Music, scholasticism and reform Salian Germany, 1024 - 1125 - McCarthy, Thomas John Henry (Manchester Univ. Press, 2009)
Making German scholarship available in English, this book deals with music as an intellectual discipline. It introduces the south-German circle, discusses dialectic and the theory of music, explores the influence of Plato, and looks at the music theory manuscripts of the 11th and 12th centuries.
Includes bibliographical references and index
Keywords: Geschichte 1024-1125; Geschichte; Gesellschaft; Musik; Music -- Instruction and study -- Germany -- History -- To 1500; Music -- Social aspects -- Germany -- To 1500; Musiktheorie; Deutschland; Germany -- History -- Franconian House, 1024-1125; Germany -- Intellectual life -- To 1500